Effects of pneumoperitoneum and of an alveolar recruitment maneuver followed by positive end-expiratory pressure on cardiopulmonary function in sheep anesthetized with isoflurane–fentanyl - Rodrigues, Jéssica C. [UNESP]; Teixeira-Neto, Francisco J. [UNESP]; Cerejo, Sofia A. [UNESP]; Celeita-Rodríguez, Nathalia [UNESP]; Garofalo, Natache A. [UNESP]; Quitzan, Juliany G. [UNESP]; Rocha, Thalita L.A. [UNESP] (Elsevier, 2017)
Objective To investigate the effects of pneumoperitoneum alone or combined with an alveolar recruitment maneuver (ARM) followed by positive end-expiratory pressure (PEEP) on cardiopulmonary function in sheep. Study design Prospective, randomized, crossover study. Animals A total of nine adult sheep (36–52 kg). Methods Sheep were administered three treatments (≥10-day intervals) during isoflurane–fentanyl anesthesia and volume-controlled ventilation (tidal volume: 12 mL kg−1) with oxygen: CONTROL (no intervention); PNEUMO (120 minutes of CO2 pneumoperitoneum); PNEUMOARM/PEEP (PNEUMO protocol with an ARM instituted after 60 minutes of pneumoperitoneum). The ARM (5 cmH2O increases in PEEP of 1 minute duration until 20 cmH2O of PEEP) was followed by 10 cmH2O of PEEP until the end of anesthesia. Cardiopulmonary data were recorded until 30 minutes after abdominal deflation. Results PaO2 was decreased from 435–462 mmHg (58.0–61.6 kPa) (range of mean values in CONTROL) to 377–397 mmHg (50.3–52.9 kPa) in PNEUMO (p < 0.05). Quasistatic compliance (Cqst, mL cmH2O−1 kg−1) was decreased from 0.85–0.92 in CONTROL to 0.52–0.58 in PNEUMO. PaO2 increased from 383–385 mmHg (51.1–51.3 kPa) in PNEUMO to 429–444 mmHg (57.2–59.2 kPa) in PNEUMOARM/PEEP (p < 0.05) and Cqst increased from 0.52–0.53 in PNEUMO to 0.70–0.74 in PNEUMOARM/PEEP. Abdominal deflation in PNEUMO did not restore PaO2 and Cqst to control values. Cardiac index (L minute−1 m2) decreased from 4.80–4.70 in CONTROL to 3.45–3.74 in PNEUMO and 3.63–3.76 in PNEUMOARM/PEEP. Compared with controls, ARM/PEEP with pneumoperitoneum decreased mean arterial pressure from 81 to 68 mmHg and increased mean pulmonary artery pressure from 10 to 16 mmHg. Conclusions and clinical relevance Abdominal deflation did not reverse the pulmonary function impairment associated with pneumoperitoneum. The ARM/PEEP improved respiratory compliance and reversed the oxygenation impairment induced by pneumoperitoneum with acceptable hemodynamic changes in healthy sheep.
Keywords: alveolar recruitment maneuver; pneumoperitoneum; sheep